Freestanding carbon encapsulated mesoporous vanadium nitride nanowires enable highly stable sulfur cathodes for lithium-sulfur batteries. (October 2017) - Li, Xingxing; Ding, Kang; Gao, Biao; Li, Qingwei; Li, Yuanyuan; Fu, Jijiang; Zhang, Xuming; Chu, Paul K.; Huo, Kaifu
Abstract: Lithium-sulfur (Li-S) battery is one of the most promising energy storage systems due to its large energy density of 2560 Wh kg −1 . However, severe shuttle effect of polysulfide intermediates, poor conductivity of S and large volume change during cycling cause fast capacity fading and poor cycle performance. Herein, we demonstrate S nanodots impregnated microporous carbon encapsulated conductive mesoporous vanadium nitride nanowires (S/MVN@C NWs) as high-performance S cathode materials for Li-S batteries. The S nanodots with the size of 2–5 nm are impregnated into the mesopores of MVN@C NWs and further encapsulated with microporous carbon. During cycling, the polysulfides intermediates are strongly chemical anchored by the conductive MVN NWs and further physically trapped by microporous carbon coating within the cathode. The freestanding and binder-free cathode comprising intertwining and interpenetrating S/MVN@C NWs demonstrates highly mechanical flexibility, which deliver a long cycle life of 636 mAh g −1 after 200 cycles at 1 C (1650 mA g −1 ) and high rate performance with a capacity of 543 mAh g −1 at 10 C. Even at a high areal mass loading of 9.7 mg cm −2, a large and stable capacity of 7.1 mAh cm −2 is achieved. The strategy combining microporous carbon coating with high conducting mesoporous metal nitrides opens a feasible route to design large-capacity and high-stability S-based cathodes for Li-S batteries. Graphical abstract: Highlights: Sulfur impregnated into carbon encapsulated mesoporous vanadium nitride nanowires. Polysulfides chemically anchored by vanadium nitride and physically trapped by carbon coating. A large capacity of 7.1 mAh cm −2 is achieved at a high mass loading of 9.7 mg cm −2 . The paper-like sulfur cathode with high rate performance is high flexibility.